COLLEGE STUDENTS’ ABILITY IN USING AFFIXATION ON FORMING WORDS - Khatimun Nisa’ Urasida; Yuli Herman; Risza Dwiputri (Universitas Mahaputra Muhammad Yamin, 2025)
This study investigates the ability of sixth-semester students in the English Education Study Program at UMMY Solok (2023/2024) to use affixation in word formation. Using a descriptive quantitative method, the study involved 17 students, divided into two groups through random sampling. Six students participated in a tryout, while ten students were selected as the research sample. Data were collected through a test assessing students' understanding of prefixes, suffixes, and their combinations. The findings indicate that students performed well with prefixes, fairly with suffixes, and poorly when combining prefixes and suffixes. Errors were most common when students were unsure of how to correctly attach affixes to root words. These results highlight the need for targeted instructional strategies to enhance students’ morphological competence. The study contributes to curriculum development and suggests incorporating additional affixation-focused materials and training. Future research may further explore affixation difficulties and their impact on linguistic proficiency.